"A Dot on a Map": Cartographies of Erasure in Garifuna Territory. Issue 2 (5th December 2018) - Brondo, Keri Vacanti
Abstract: This article explores the complexities of territorial dispossession in a post‐Washington‐Consensus global development policy context. In particular, it explores a contemporary development paradox in Honduras: the transnational recognition of the rights of indigenous people alongside massive land dispossession of the Afro‐Indigenous Garifuna in the name of development. Cartography is considered both in terms of physical mapping projects and ideological boundary‐making through rhetorical dispossession. In state‐sponsored communal mapping projects from the late 1990s into the early 2000s, the Garifuna were denied both currently inhabited land and that which they historically accessed. Anything that sat beyond mapped borders became "open" to foreign purchase. Legislation passed after the 2009 coup d'état further erased the Garifuna's historical occupation of coastal lands by embracing "model city" development and megatourism. Despite post–Washington Consensus development discourses of equality and official rhetoric of inclusion and celebration of indigenous rights, this case study demonstrates cartographic processes continue to erase Garifuna historical rights to territory.